Use of the Azoll plant (Azolla pinnata) in Broiler Diets and its effect on the Microbial Content of the Intestine and Carcass Characteristics - Al-Hamed, Anwar Mohammed Yonis; Al-Husseiny, Nihad AbdulAljabbar (Journal of agricultural, environmental and veterinary sciences, 2023)
This study was conducted in the poultry field of the Department of Animal Production - College of Agriculture and Forestry - University of Mosul, one-day-old unsexed chickens (Ross 308) were used, and from the first day of receiving the chicks, they were distributed randomly to the study treatments, which was represented by adding three different percentages of dried Azolla (Azolla pinnata), with three replications/treatment, as follows: T1 (control): a standard diet free of Azolla T2: standard diet +4.5% azolla T3: standard diet 9.0+% azolla T4: Standard Diet + 13.5% Azolla The results of the statistical analysis were: a decrease in the numbers of Salmonella and E. coli, the percentage of neck and abdominal fat, with a significant increase in the numbers of lactobacillus, the percentage of thighs, back, length of intestines, and two cecum when adding Azolla by (9.0, 13.5)%, Compared to control and there was no significant differences in carcass yield and dressing% and edibles eat between the treatments. The addition of dried Azolla Substitute was part of the protein diet as a nutritional management method used to use a locally available protein source.